PENERAPAN DIGITAL MARKETING PADA PELAKU UMKM DI DESA MAGUWAN PONOROGO - Anggraini, Yulia; Mustofa Anshori , Rodhi; Vebri Permatasari , Sindy (Proceedings of Annual Conference on Community Engagement, 2023)
Digital marketing training has proven to be an effective way to improve and expand the reach of a product and to increase sales. But the understanding and reach of digital marketing has not spread evenly, especially to MSME players in Maguwan Village, Sambit District, Ponorogo Regency. Even less familiar in using social media as a medium for online shopping in e-commerce and this familiarity must be increased which is then used as a tool for developing marketing strategies carried out by MSME players. This study aims to increase sales of Maguwan Village MSMEs on social media such as shopee, tiktok shop and also Facebook. The research method used in this research is a qualitative method using the Asset Based Community Development technique, the data collection process is carried out by means of interviews and observations with MSME players in Maguwan Village. The results of this study indicate a positive response from MSME actors with competent resource persons presented in improving skills.